Facebook Usage Patterns and its Impact on the Academic Performance of University Students - Manzoor, Sajid; Ahmed, Zamir (PJDOL, 2024)
The study focused on understanding the different patterns of Facebook usage among university students and its impact on their academic performance. It was examined that to what extent Facebook consumption influenced the students’ educational performance. "Uses and Gratifications" a theoretical framework was used to analyze consumption patterns. It was a quantitative research design employed, and the data was collected from 250 university students by using a purposive sampling technique. The results showed that heavy uses of Facebook was related to addictive behavior among university students, negatively affecting their educational performance. These impacts led to different negative effects such as poor time management, procrastination, and a decrease in productive academic activities. It was supported by the p-value 0.00, confirming that increased Facebook consumption significantly correlated with decreased academic performance. Parents, teachers, and authorities must put concerted efforts to regulate social media use through healthy boundaries, digital literacy, and time management skills. Parents can monitor and guide children's digital habits; teachers can incorporate lessons on balanced usage and even make social media an educational tool.